2006
DOI: 10.1128/mcb.01854-05
|View full text |Cite
|
Sign up to set email alerts
|

A Distant Upstream Locus Control Region Is Critical for Expression of the Kit Receptor Gene in Mast Cells

Abstract: The Kit receptor tyrosine kinase functions in hematopoiesis, melanogenesis, and gametogenesis and in interstitial cells of Cajal. We previously identified two upstream hypersensitive site (HS) clusters in mast cells and melanocytes. Here we investigated the roles of these 5 HS sequences in Kit expression using transgenic mice carrying Kit-GFP reporter constructs. In these mice there is close correspondence between Kit-GFP reporter and endogenous Kit gene expression in most tissues analyzed. Deletion analysis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…The inversion included a regulatory locus located approximately 150kb upstream of Kit that controls the expression of this receptor in mast cells, and elegant experimental work demonstrated that interference with this regulatory element is the probable cause for mast cell deficiency in the W sh mouse. 16 The current results provide an improved understanding of the W sh inversion. The 3Ј end of the inversion resides 67.5 kb 5Ј to the coding region of Kit in a region devoid of known genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inversion included a regulatory locus located approximately 150kb upstream of Kit that controls the expression of this receptor in mast cells, and elegant experimental work demonstrated that interference with this regulatory element is the probable cause for mast cell deficiency in the W sh mouse. 16 The current results provide an improved understanding of the W sh inversion. The 3Ј end of the inversion resides 67.5 kb 5Ј to the coding region of Kit in a region devoid of known genes.…”
Section: Discussionmentioning
confidence: 99%
“…null, the other impaired) at the Kit locus W (white spotting), while the W sh mouse carries an incompletely characterized inversion upstream of Kit that affects a key regulatory element. [11][12][13][14][15][16] Mice with mutations affecting Kit (rather than SCF) are particularly useful because they can be engrafted with cultured mast cells. 17,18 An abnormal phenotype that can be corrected with such engraftment may presumptively be attributed to mast cell deficiency.…”
mentioning
confidence: 99%
“…The 59 breakpoint of this inversion disrupts the Corin gene, leading to cardiac hypertrophy, and the 39 breakpoint is located 72 kbp upstream of the c-Kit transcriptional start site (14,15). Regulatory elements driving the expression of c-Kit in mast cells were mapped within the affected region (16). Thus, it can be assumed that the inversion or additional deletions of cis regulatory elements prevent mast cell-specific c-Kit expression, which ultimately leads to their irreversible demise within a few weeks after birth of sash mice (17,18).…”
mentioning
confidence: 99%
“…33 These data suggest that upstream sequences are involved in Kit activity, 33 although, unexpectedly, large transgenic constructs including them are very poorly expressed in bone marrow cells. 34 Notably, the upstream sequences are dispensable in our construct. It is possible that these sequences might be involved in a different level of regulation than the promoter and first intron sequences, perhaps controlling chromatin structure and accessibility of the proximal sequences to the transcriptional machinery, rather than directly affecting their activity.…”
Section: The Kit/gfp Transgene Includes Sequences Controlling Gene Exmentioning
confidence: 99%